Nedd4 controls animal growth by regulating IGF-1 signaling - Cao, Xiao R; Lill, Nancy L; Boase, Natasha; Shi, Peijun P; Croucher, David R; Shan, Hongbo; Qu, Jing; Sweezer, Eileen M; Place, Trenton; Kirby, Patricia A; Daly, Roger J; Kumar, Sharad; et al. (Science signaling, 2008)
The ubiquitin ligase Nedd4 has been proposed to regulate a number of signaling pathways, but its physiological role in mammals has not been characterized. Here we present an analysis of Nedd4-null mice to show that loss of Nedd4 results in reduced insulin-like growth factor 1 (IGF-1) and insulin signaling, delayed embryonic development, reduced growth and body weight, and neonatal lethality. In mouse embryonic fibroblasts, mitogenic activity was reduced, the abundance of the adaptor protein Grb10 was increased, and the IGF-1 receptor, which is normally present on the plasma membrane, was mislocalized. However, surface expression of IGF-1 receptor was restored in homozygous mutant mouse embryonic fibroblasts after knockdown of Grb10, and Nedd4(-/-) lethality was rescued by maternal inheritance of a disrupted Grb10 allele. Thus, in vivo, Nedd4 appears to positively control IGF-1 and insulin signaling partly through the regulation of Grb10 function.